Introduction to electron microscopy for biologists - Allen, Terence D. (Terence David), 1944-; ScienceDirect eBooks (London ; Boston : Elsevier : Academic, 2008)
This volume demonstrates how electron microscopy contributes to knowledge about biological structural information.
Part I: Exploring the Organisation of the Cell by Electron Microscopy --Section 1: Basic Transmission and Scanning Electron Microscopy --Part II: Electron Microscopy of Specific Cellular Structure -- Section 1: The Cell Membrane -- Section 2: The Cytoskeleton -- Section 3: Extracellular Matrix and Cell Junctions -- Section 4: The Nucleus -- Part III: Cells and Infectious Agents.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Electron microscopy -- Technique; Cytology -- Technique; Microscopy, Electron -- methods; Cytological Techniques; SCIENCE -- Life Sciences -- Cell Biology; Cytology -- Technique; Electron microscopy -- Technique; Electronic books